In vitro cytotoxicity of superparamagnetic iron oxide nanoparticles on neuronal and glial cells. Evaluation of nanoparticle interference with viability tests - Costa, Carla (2016)
Superparamagnetic iron oxide nanoparticles (ION) have attracted great interest for use in several biomedical fields. In general, they are considered biocompatible, but little is known of their effects on the human nervous system. The main objective of this work was to evaluate the cytotoxicity of two ION (magnetite), coated with silica and oleic acid, previously determining the possible interference of the ION with the methodological procedures to assure the reliability of the results obtained. Human neuroblastoma SHSY5Y and glioblastoma A172 cells were exposed to different concentrations of ION (5-300 µg ml(-1) ), prepared in complete and serum-free cell culture medium for three exposure times (3, 6 and 24 h). Cytotoxicity was evaluated by means of the MTT, neutral red uptake and alamar blue assays. Characterization of the main physical-chemical properties of the ION tested was also performed. Results demonstrated that both ION could significantly alter absorbance readings. To reduce these interferences, protocols were modified by introducing additional washing steps and cell-free systems. Significant decreases in cell viability were observed for both cell lines in specific conditions by all assays. In general, oleic acid-coated ION were less cytotoxic than silica-coated ION; besides, a serum-protective effect was observed for both ION studied and cell lines. These results contribute to increase the knowledge of the potential harmful effects of ION on the human nervous system. Understanding these effects is essential to establish satisfactory regulatory policies on the safe use of magnetite nanoparticles in biomedical applications.